Implications of the Shifts in Geo-Economic Center of Gravity and the ASEAN Charter on the Accounting Profession and Accounting Regulation in Indonesia (2010 National Accounting Symposium Keynote Speech) - BAMBANG SUDIBYO (The Indonesian Journal of Accounting Research, 2013)
The hypothetical ongoing shift of geo-economic center of gravity from the developed economies concentrated in the West to the emerging economies concentrated in the East, given that it was true, is very interesting and is supposed to bring pervasive and strategic implications to the Indonesian economy, business and accounting world. The ASEAN Charter 2007, ratified by the Indonesian Parliament in 2008, was committed by ASEAN leaders during the hypothetical shift. The Charter commits ASEAN 10 member countries to become one solid economic community, one solid socio-cultural community and one solid security community by 2015. This article refers to a secondary data based economic policy research on the shift and the Charter, and their bearings and implications on the accounting profession, financial accounting regulation and standard setting in Indonesia. In addition, the author also develops a theology of happenings which affirms the aforesaid shift.